Analisis Ragam dan Peragam Bobot Badan Kambing Peranakan Etawa (ANALYSIS VARIANCE AND COVARIANCE OF BODY WEIGHT OF ETTAWA GRADE GOAT) - Hidayati, Siti; Kurnianto, Edy; Johari, Seno (Jurnal Veteriner, 2015)
The aims of this study were (1) to analyze the phenotypic performance of Ettawa Grade (EG) goat; (2)to estimate the heritability of birth weight (BW), weaning weight (WW), yearling weight (YW), and geneticcorrelation between two body weights on the third different period; and (3) to analyze the variance andcovariance component of body weight. The material used were the exiting records of 437 EG goats in BalaiPembibitan Ternak Unggul dan Hijauan Pakan Ternak Pelaihari, South Kalimantan. These goats originatedfrom the crossing between 19 males and 216 females from periods of 2009 - 2012. Nested Design methodwas used to etimate the phenotypic correlation, heritability and genetic correlation. Variance componentswere determined from heritability estimation, while covariance components were determined from geneticcerrelation estimation. Phenotypic correlation between BW and WW, between BW and YW, and betweenWW and YW were 0.19 (low); 0.31 (medium); 0.65 (high); respectively. Heritability of BW, WW, and YW were0.43±0.23 (high); WW 0.27±0.19 (medium); and YW 1.01±0.38 (excludeof the h2 value), respectively.Genetic correlation between BW and WW, between BW and YW, and between WW and YW were -0.04(negative low); 0.49 (positive medium); and -0.41 (negative medium), respectively. Variance components ofbuck, ewes, and kid for BW were 10.76%; 37.16%; and 52.09%, respectively, for WW were 6.67%; 38.52%;and 54.81%, respectively, and for YW were 25.15%; 58.37%; and 16.43%, respectively. Covariancecomponents of buck, ewes, and kid between BW and WW were -3.91%; 66.45%; and 37.46%, respectively,between BW and YW were 65.68%; 16.50%; and 17.82, and between WW and YW were -5.14%; 83.87%; and21.28%, respectively. In conclusions variance component of ewes and kid were high in body weight at birthand weaning time. Therefore, selection should be conducted for body weight at birth and weaning time.
Keywords: Ettawa Grade, phenotypic correlation, heritability, genetic correlation, body weight, variance and covariance components